Claustral MeCP2 Regulates Methamphetamine-induced Conditioned Place Preference in Cynomolgus Monkey - 배진희; 안수진; 조두완; 김현선; 한수철; 임혜인 (한국뇌신경과학회, 2022)
The claustrum, a brain nucleus located between the cortex and the striatum, has recently been highlighted in drug-related reward processing. Meth- yl CpG-binding protein-2 (MeCP2) is a transcriptional regulator that represses or activates the expression of the target gene and has been known to have an important role in the regulation of drug addiction in the dopaminergic reward system. The claustrum is an important region for regulat- ing reward processing where most neurons receive dopamine input; additionally, in this region, MeCP2 is also abundantly expressed. Therefore, here, we hypothesized that MeCP2 would be involved in drug addiction control in the Claustrum as well and investigated how claustral MeCP2 regulates drug addiction. To better understand the function of human claustral MeCP2, we established a non-human primate model of metham- phetamine (METH) - induced conditioned place preference (CPP). After a habituation of two days and conditioning of ten days, the CPP test was conducted for three days. Interestingly, we confirmed that virus-mediated overexpression of MECP2 in the claustrum showed a significant reduc- tion of METH-induced CPP in the three consecutive days during the testing period. Moreover, they showed a decrease in visit scores (frequency for visit) for the METH-paired room compared to the control group although the scores were statistically marginal. Taken together, we suggest that the claustrum is an important brain region associated with drug addiction, in which MeCP2 may function as a mediator in regulating the response to addictive drugs.